Assessment of Quality of Life in Acne Vulgaris Patients in Terms of Clinical Severity and Psychological Burden: A Multi Centre Study in Anand District (Bangladesh Journal of Medical Science, 2025)
Background The term “acne” is derived from the Greek word “acme,” meaning “point” or “spot.” Acne vulgaris is one of the most common chronic dermatological conditions, predominantly caused by the Gram-positive anaerobic bacterium Cutibacterium acnes. It affects individuals across various age groups, with a significant impact on physical appearance, quality of life (QoL), and psychological well-being. Methodology This cross-sectional, observational study was conducted from December 2021 to March 2022, involving individuals aged 18–30 years diagnosed with acne vulgaris. Patients visiting a dermatology clinic were assessed for clinical severity, QoL impairment, and psychological burden using a validated, self-administered questionnaire. Results A total of 171 patients were enrolled in the study, with a mean age of 24.83 ± 2.92 years. The cohort comprised 45 males and 126 females, with a positive family history of acne in 82 participants. Assessment of QoL impact revealed that 101 patients experienced a moderate effect, while 66 reported a very large impact on daily life. Clinical grading of acne showed that 12 patients had mild acne, 104 had moderate acne, 54 had severe acne, and 1 patient presented with very severe acne. Psychological evaluation indicated that individuals with moderate to severe acne exhibited mild to moderate depressive symptoms. Additionally, 147 patients reported experiencing a moderate psychological burden associated with their condition. Conclusion Acne vulgaris significantly affects patients’ QoL, with the majority experiencing moderate impairment. The condition is linked to emotional distress, including feelings of embarrassment, aggression, and negative self-perception regarding facial appearance. Given its psychosocial impact, an integrated approach focusing on dermatological management and psychological support is essential for improving patient outcomes.BJMS, Vol. 24 No. 04 October’25 Page : 1106-1113